The role of cuticular hydrocarbons in forensic entomology: a mini review / Meenakshi Bharti - Bharti, Meenakshi (Faculty of Medicine, Universiti Teknologi MARA, 2021)
The cuticular hydrocarbons (CHCs) are expressed on insect cuticle and provide protection from desiccation and abrasion. The CHC profiles are species-specific and vary in each insect. Forensic entomologists have utilized varying expressions of CHCs to determine the age as well as to delimit insects. This review focuses on the role of CHCs in species identification and aging in the field of forensic entomology.